Setting the Ground for Global City Formation: Neoliberalisation and Local Elites in Frankfurt on the Main - Mössner, Samuel; Freytag, Tim (Quaestiones Geographicae, 2014)
This paper approaches the global city concept from a local perspective taking into account the political action of local elites in times of urban neoliberalisation. Drawing on the empirical research carried out in Frankfurt (Main), we argue that the very beginnings of the global city formation were less a result of global processes superseding local ones, as is often argued, but rather emerged out of local political action contested by local protests. In the first part, we will revisit the global city concept and contrast it against a critique of urban neoliberalisation. The second focuses on reviewing the history of urban restructuring in the Frankfurt Westend during the 1960s and 1970s. We suggest that the transformation of the Westend into a “strategic site of global control” (Sassen 2011) has been constructed as a narrative in order to legitimise local forms of real estate speculation, marketisation of commodification. Our paper tries to unfold the logics and strategies of such neoliberal urbanisation by critically reflecting upon historical events since the 1960s